(untitled) (Fourth World Journal, 2011)
This article examines observer participation in the WIPO Intergovernmental Committee on Intellectual Property, Genetic Resources, Traditional Knowledge, and Folklore. It discusses existing participation mechanisms and stresses the need for effective protection of genetic resources, traditional knowledge, and cultural expressions, particularly for Indigenous peoples. The article advocates for the full and meaningful involvement of Indigenous peoples in international decision-making processes. Drawing connections to the UN Declaration on the Rights of Indigenous Peoples, it highlights the importance of aligning intellectual property frameworks with international human rights standards. The article also references relevant instruments such as the Nagoya Protocol, emphasizing that Indigenous participation is essential for safeguarding their rights and cultural heritage within global intellectual property regimes.